Stimuli-Responsive Nodal Dual-Drug Polymer Nanoparticles for Cancer Therapy - Kuang G; Ding J; Xie W; Ye Z; Zhang Q (International Journal of Nanomedicine)
Gaizhen Kuang,1,2 Jiaze Ding,1,2 Weiyi Xie,1,2 Zihui Ye,1,2 Qingfei Zhang1,2 1The First Affiliated Hospital, Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of China; 2School of Basic Medical Sciences, Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of ChinaCorrespondence: Gaizhen Kuang, Wenzhou Medical University, Wenzhou, Zhejiang, 325000, People’s Republic of China, Email gzhkuang@wmu.edu.cn Qingfei Zhang, Wenzhou Medical University, Wenzhou, Zhejiang, 325000, People’s Republic of China, Email 654626160@qq.comBackground: Polymeric drug delivery systems (DDSs) have gained significant attention in cancer therapy. However, these systems often respond to a single biological stimulus in tumor tissues or cells, limiting their effectiveness. While multi-sensitive DDSs improve therapeutic precision, their complex synthesis involving multi-step modifications remains challenging. Developing functionally integrated and simplified multiple stimuli-responsive DDSs is crucial to addressing tumor diversity and enhancing treatment efficacy.Methods and Results: Here, we develop a dual-sensitive nodal dual-drug polymer nanoparticle (DDPoly NP) system for cancer therapy. This system combines a platinum(IV) prodrug (Cisplatin(IV)) with Demehylcantharidin (DMC) to create a dual-drug molecule (DDM). Then DDM is conjugated with methoxypolyethylene glycol (MPEG), forming a nodal dual-drug polymer (DDPoly). The amphiphilic polymer is capable of self-assembling into nanoparticles (DDPoly NPs) when in aqueous solution. The drug release experiments displayed that lower pH and reductive conditions simulating tumor microenvironment promoted the release of Cisplatin and DMC. Cytotoxicity studies demonstrated that DDPoly NPs exhibited superior anti-cancer activity compared to the single-drug system (SDPoly NPs). The IC50 values of DDPoly NPs against A549 cells (15.37 μM) and HeLa cells (17.05 μM) were significantly lower than those observed for SDPoly NPs, which were 40.48 μM for A549 cells and 38.11 μM for HeLa cells, respectively.Conclusion: The study developed dual stimuli-responsive DDPoly NPs based on acid- and reduction-sensitive DDM, enabling tumor-specific activation without additional responsive components. DDPoly NPs triggered Pt(II) release via reduction and generated DMC through acid hydrolysis. The synergistic effect of DDPoly NPs lies in that DMC could inhibit the expression of serine/threonine protein phosphatase 2A (PP2A) and further elevate the expression of hyper-phosphorylated Akt (pAKt), thus blocking DNA repair to enhance Pt(II)-induced apoptosis. DDPoly NPs showed enhanced anti-cancer efficacy against cancer cells compared to SDPoly NPs, highlighting its potential for nanomedicine development.Keywords: platinum drug, cancer therapy, chemotherapy, polymer nanoparticle, stimuli-responsive